Visualization skills in elite junior tennis players - Radu Predoiu; Rareș Stănescu; Mathias Alberton; Costel Curcă; Ionuț Patenteu; Răzvan Marian Bucătaru (INSPIREE: Indonesian Sport Innovation Review, 2025)
The  purpose  of  the study. The aim of the research is to examine the relevance of visualization skills in elite junior tennis players. Materials and methods. Twenty-six junior tennis players, boys and girls (Mage = 13.88), of which eight players ranked 1st or 2nd in the national rankings in Romania (having, also, very good results at European level) took part in the study. The Sport Imagery Ability Questionnaire (SIAQ) was used to assess tennis players’ imagery ability. Results. The Kruskal-Wallis H test and the Dwass-Steel-Critchlow-Fligner pairwise comparison test were used. Elite tennis players have significantly better Goal imagery abilities (p = 0.042) and Affect imagery abilities (p = 0.006), compared to athletes ranked between 7th and 15th in the national ranking. Also, using the Mann-Whitney (U) test gender-related differences in terms of visualization skills were explored. Conclusions. Tennis players ranked 1st and 2nd in the national ranking can easily imagine the emotions and excitement associated with performing, observing themselves (mentally) more easily winning a medal or a competition. Even if no significant gender-specific differences were found, female athletes reported slightly greater ease in visualizing skills and strategies/game plans, compared to male junior tennis players.